2010
DOI: 10.1186/1477-7819-8-48
|View full text |Cite
|
Sign up to set email alerts
|

Late local recurrence of dermatofibrosarcoma protuberans in the skin of female breast

Abstract: Dermatofibrosarcoma protuberans (DFSP) of the breast is exceptionally obscure and late local recurrence of this entity on this site is even more uncommon. We describe such a case in a 48-year-old woman, who at the age of 35 had a DFSP excised from her right breast. Thirteen years later, she developed an ovoid mass in her right breast over the postsurgical scar area. Wide local excision of the tumor with generous tissue margin was performed and microscopic and immunohistochemical findings established the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…DFSP mainly occurs between the second and fifth decade of life [5]. There are reports of lesions in areas that suffered previous trauma or in patients who underwent several previous surgeries [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFSP mainly occurs between the second and fifth decade of life [5]. There are reports of lesions in areas that suffered previous trauma or in patients who underwent several previous surgeries [13].…”
Section: Discussionmentioning
confidence: 99%
“…The local recurrence rate tends to decrease with the increase of surgical margins [5]. This procedure can generate cosmetic deformities and even functional damage.…”
Section: Discussionmentioning
confidence: 99%
“…DFSP is a rare, slow growing, infiltrating dermal neoplasm of intermediate malignancy and is composed of spindle shaped tumour cells arranged in storiform pattern. It is often found in the extremities and trunk of adults,2 3 less commonly in the adult female breasts1 3–5 and recently reported in the breast of a 2-year-old girl 6. There are a few characteristics to differentiate DFSP from other dermatofibromas.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed a variety of surgical approaches to address DFSP of the breast. One patient underwent a mastectomy, one patient underwent a wide local excision with concomitant breast reduction, three patients underwent a wide local excision with fl ap reconstruction, one patient underwent a wide local excision with skin graft, and nine patients underwent wide local excision with primary closure ( Table 1 , [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Th e reconstructive challenge in DFSP of the breast is to balance the oncologic principles of adequate resection with the cosmetic goals of acceptable symmetry and contour.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Th e most common location of DFSP is the trunk, with 25% of cases aff ecting the chest and shoulder areas (1). At least 40 case reports of DFSP in the breast have been reported, but less than half address the surgical management (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which we describe here.…”
mentioning
confidence: 99%